2018
DOI: 10.21653/tjpr.416625
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Postural Control and Hand Function in the Subjects Aged 65 Years and Over

Abstract: This study was aimed to investigate the relationship between postural control and hand function in the elderly.Methods: One hundred-five elderly individuals that are 65 years old or over and living in a nursing home were included in the study. Postural control status (Berg Balance Scale) and hand function (manual dexterity: Nine Hole Peg Test, hand grip strength: handheld dynamometer, pinch grip strength: pinchmeter) of elderly individuals were evaluated. Results:The mean age of the subjects was 76.59±6.92 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…HGS was the most studied measure with six of six studies reporting positive associations with balance. The associations were strong (three studies, n = 439) [ 21 , 53 , 54 ], medium (two studies, n = 529) [ 28 , 55 ] and weak (one study n = 209) [30]. The six studies were rated good or moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…HGS was the most studied measure with six of six studies reporting positive associations with balance. The associations were strong (three studies, n = 439) [ 21 , 53 , 54 ], medium (two studies, n = 529) [ 28 , 55 ] and weak (one study n = 209) [30]. The six studies were rated good or moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, core stability created by the activation of core muscles is important and essential for many upper extremity activities (9). It has been demonstrated that there is a positive relationship between upper extremity functions and postural control in children, older people, and Parkinson's patients (10)(11)(12). In addition, impaired upper extremity function was also found to be associated with decreased postural control in PwMS, even mild disabilities (13).…”
Section: Introductionmentioning
confidence: 99%